Expanded Mesenchymal Stem Cell Therapy for Symptomatic Knee Osteoarthritis - Hassan Mubark (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
Our objective in this study is to determine if the cellular biological treatment can replace surgery by controlling the symptoms, stopping, or slowing the progression of osteoarthritis (OA), and repairing defects. Bone marrow oedema and subchondral bone cysts are frequent findings in the various stages of knee OA. Typically seen on MRI imaging, once the degenerative process starts, it progresses to severe OA, then a high chance of metal knee replacement. There is no proven therapy yet to alter the outcome of OA. Herein we report a case of a fifty-four-year-old salesperson who enjoys active sports. He presented with symptomatic right knee OA. His knee MRI scan revealed patellofemoral subchondral bone marrow oedema and multiple subchondral cysts. Medial meniscus tear, medial, and patellofemoral cartilage loss. He had a large baker cyst and synovitis. He did not respond to an ultrasound-guided steroid injection. Still, he responded dramatically to a single dose of autologous fat-derived expanded mesenchymal stem cells (MSCs) combined with platelet-rich plasma (PRP). He became symptoms-free three months post the therapy, and that persisted. A repeat MRI nine months after the treatment showed a tiny baker cyst and significant reduction of synovitis due to an anti-inflammatory effect of MSCs. Thirty-three months post-therapy follow-up MRI revealed full resolution of both bone marrow oedema and multiple subchondral patellofemoral bone cysts. This case showed encouraging results, which might change the way we practice medicine in OA management as a step before considering surgery.